2007
DOI: 10.1111/j.1399-3089.2007.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

WZS‐pig is a potential donor alternative in corneal xenotransplantation

Abstract: Rejection of pig-rhesus xenografts occurred early in penetrating corneal transplantation, but not in lamellar corneal transplantation. The endothelium of the xenograft might be a primary target of immune attack. Corticosteroid treatment inhibited rejection of the corneal xenografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 12 publications
(15 reference statements)
7
67
3
Order By: Relevance
“…13 In fact, Pan et al reported that HAR did not occur immediately after a pig-to-rhesus corneal transplantation, although they did not evaluate the expression of xenoantigens. 37 Accordingly, the expression of α-Gal and non-Gal antigens on cultivated corneal cells in this study may not be a direct clue to indicate the involvement of these xenoantigens in the immune rejection after corneal xenotransplantation. Nevertheless, we believe that the characterization of pig corneal cells in the present and future work would have a significant value as the basic data for potential use of pig cornea for human substitution.…”
Section: Current Eye Researchmentioning
confidence: 87%
“…13 In fact, Pan et al reported that HAR did not occur immediately after a pig-to-rhesus corneal transplantation, although they did not evaluate the expression of xenoantigens. 37 Accordingly, the expression of α-Gal and non-Gal antigens on cultivated corneal cells in this study may not be a direct clue to indicate the involvement of these xenoantigens in the immune rejection after corneal xenotransplantation. Nevertheless, we believe that the characterization of pig corneal cells in the present and future work would have a significant value as the basic data for potential use of pig cornea for human substitution.…”
Section: Current Eye Researchmentioning
confidence: 87%
“…Owing to the small size, simple operation, and striking similarities to man with respect to anatomy and physiology, minipigs are commonly used as experimental animals in research on the cardiac and vascular system, digestive system, reproductive system, dermatology, and nutriology (13) Among them, the WZS minipig was the first to be cultivated and inbred after being introduced from Wuzhishan, Hainan, China in 1987 (14). After 20 generations of inbreeding, the WZS minipig now has the highest inbreeding coefficient (more than 0.965) (15), stable heredity, and little variability between individual animals.…”
Section: Introductionmentioning
confidence: 99%
“…This approach, suffers a number of limitations including a shortage of suitable donor tissue in many countries. In recent years, corneal tissue engineering has emerged as a promising alternative to transplantation and significant progress has been made in this area with keratoprostheses (4,5), xenografts (6)(7)(8) and tissue-engineered corneas (9) entering clinical or pre-clinical development.…”
Section: Introductionmentioning
confidence: 99%